Acute toxicity, uptake and accumulation kinetics of nickel in an invasive copepod species: Pseudodiaptomus marinus. (February 2016) - Tlili, Sofiène; Ovaert, Julien; Souissi, Anissa; Ouddane, Baghdad; Souissi, Sami
Abstract: Pseudodiaptomus marinus is a marine calanoid copepod originating of the Indo-Pacific region, who has successfully colonized new areas and it was recently observed in the European side of the Mediterranean Sea as well as in the North Sea. Actually, many questions were posed about the invasive capacity of this copepod in several non-native ecosystems. In this context, the main aim of this study was to investigate the tolerance and the bioaccumulation of metallic stress in the invasive copepod P. marinus successfully maintained in mass culture at laboratory conditions since 2 years. In order to study the metallic tolerance levels of P. marinus, an emergent trace metal, the nickel, was chosen. First, lethal concentrations determination experiments were done for 24, 48, 72 and 96 h in order to calculated LC50% but also to select a relevant ecological value for the suite of experiments. Then, three types of experiments, using a single concentration of nickel (correspond the 1/3 of 96 h-LC50% ) was carried in order to study the toxico-kinetics of nickel in P. marinus . Concerning lethal concentrations, we observed that P. marinus was in the same range of sensitivity compared to other calanoid copepods exposed to nickel in the same standardized experimental conditions. Results showed that the uptake of nickel in P. marinus depends from the pathways of entrance (water of food), but also that Isochrysis galbana, used as a food source, has an important bioaccumulation capacity and a rapid uptake of nickel. Highlights: Lethal concentrations were determined in P seudodiaptomus marinus exposed to nickel. Accumulation kinetics and nickel uptake were studied in P. marinus in presence and absence of food. The uptake of nickel in P. marinus depends from the pathways of entrance (direct absorption or into food). Isochrysis galbana has an important bioaccumulation capacity and a rapid uptake of nickel.